538. Integrase Inhibitor-Based HAART Is Associated with Greater BMI Gains in Blacks, Hispanics, and Women. (26th November 2018) - Bedimo, Roger; Adams-Huet, Beverley; Taylor, Barbara S; Lake, Jordan; Luque, Amneris
Abstract: Background: While older protease inhibitors (PI) were more likely to lead to isolated central fat accumulation, progressive increases in generalized obesity in HIV-infected patients following HAART initiation have been observed with most modern regimens, with greater increases in body mass index (BMI) reported in women and with integrase inhibitors (INSTI) use. We sought to analyze changes in BMI following initiation of HAART in a large urban HIV clinic and identify predictors of BMI changes. Methods: All patients initiating HAART at the clinic from 2009 to 2017 were included in the analysis. Exposure to HAART was defined as concurrent receipt of at least two nucleoside reverse transcriptase inhibitors (NRTI) plus at least one PI, non-nucleoside reverse transcriptase inhibitor (NNRTI) or INSTI. The effects of sex, race, and ethnicity on changes in BMI (kg/m 2 ) per year on HAART were examined using mixed-effects random regression. Results: Among the 4, 048 patients initiating HAART, 69% were male, 53% Black (B), 28% Hispanic (H), and 16% non-Hispanic Whites (NHW). Mean age was 46.3 years (SD 11.9) and mean BMI was 27.0 (6.4). Median follow-up time on HAART was 6.7 years. Cumulative exposure to NNRTI, PI, and INSTI-based HAART were 3, 546, 6, 184, and 3, 090 person-years respectively. The BMI slope per year of HAART exposure by regimen type, sex, race, and ethnicity are presented in Table 1 and Figure 1. There was no significant interaction between sex and race/ethnicity on BMI. Proportion of overweight/obese (BMI ≥ 25) increased from 51% at HAART initiation to 65% at year 3 ( P < 0.001) (Figure 2). Conclusion: INSTI-based HAART is associated with greater increases in BMI in Blacks and Hispanics. Women had greater BMI gains than men on both PI- and INSTI-based HAART. The mechanisms of these differential effects by sex and race/ethnicity should be examined in prospective studies. Disclosures: R. Bedimo, ViiV Healthcare: Consultant and Grant Investigator, Consulting fee and Research grant. Merck & Co.: Consultant and Grant Investigator, Consulting fee and Research grant. Bristol Myers Squibb: Grant Investigator, Research grant. Gilead Sciences: Consultant, Consulting fee. J. Lake, Gilead Sciences: Consultant and Grant Investigator, Consulting fee and Research grant. Merck & Co.: Consultant, Consulting fee.